Lysyl oxidase-like 2 promotes the survival, migration, and ferroptosis of endometrial cancer cells by activating the phosphoinositide 3-kinase/protein kinase B pathway - Jiashi Gu; Huanmei Sun; Juan Shao; Hu Zhang; Zhanpeng Zhu; Dongqin Ma; Yingchun Duan (Iranian Journal of Basic Medical Sciences)
Objective(s): LOXL2, known as Lysyl oxidase-like 2, is classified as a lysyl oxidase (LOX) family member. However, its role and mechanism in endometrial cancer (EC) are unknown. Therefore, we aimed to investigate the potential role and mechanism of LOXL2 in EC.Materials and Methods: The levels of LOXL2 expression in EC tissues and normal adjacent tissues were evaluated by immunohistochemically (IHC) labeling. Following the dye application, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and Transwell methodologies were executed to evaluate the effects of LOXL2 inhibition and up-regulation on the growth, programmed cell death, migration, and susceptibility to iron-dependent cell death of EC. Moreover, protein analysis through Western blotting and gene expression analysis using Real-time quantitative PCR (RT-qPCR) was employed to measure the levels of pertinent biomarkers.Results: LOXL2 is highly expressed in both EC tissues and serum in vivo. Silencing LOXL2 reduced EC cell proliferation and migration while increasing apoptosis in vitro. LOXL2 silencing increased the ferroptosis-related proteins Solute Carrier Family 7 Member 11 (SLC7A11) and Ferritin Heavy Chain 1 (FTH1) while decreasing Glutathione Peroxidase 4 (GPX4) (both, P<0.001). Additionally, LOXL2 silencing reduced the p-PI3K and p-Akt protein expression, while LOXL2 overexpression (OE-LOXL2) elevated the p-PI3K and p-Akt protein expression (both, P<0.001). Additionally, LOXL2 silencing increases SLC7A11 and FTH1 while decreasing GPX4 (both P<0.001). LOXL2 overexpression has the opposite effect. However, the LY294002 inhibitor restores SLC7A11 and FTH1 expression while decreasing GPX4 (P<0.001).Conclusion: Our research demonstrated that LOXL2 might protect EC via phosphorylation by activating the PI3K/AKT pathway.